Belgium : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
The 2014 Article IV Consultation discusses economic developments and policies in Belgium. It highlights that despite its resilience, the Belgium economy has been losing competitiveness due to higher labor cost and lower productivity growths than peer countries. The government has taken measures to close the wage gap, but it is highlighted that the economy also needs to become more productive and adaptable through deeper product and labor market reforms. The supervisory and regulatory frameworks are being strengthened with a new draft banking law that restrains trading activities and improves the recovery and resolution framework.